Warning Messages in Crisis Communication: Risk Appraisal and Warning Compliance in Severe Weather, Violent Acts, and the COVID-19 Pandemic - Rahn, Maxi; Tomczyk, Samuel; Schopp, Nathalie; Schmidt, Silke (Frontiers in Psychology, 2021)
Background: In crisis communication, warning messages are key to informing and galvanizing the public to prevent or mitigate damage. Therefore, this study examines how risk appraisal and individual characteristics influence the intention to comply with behavioral recommendations of a warning message regarding three hazard types: COVID-19 pandemic, violent acts, and severe weather. Method: A cross-sectional survey examined 403 German participants from 18 to 89 years (M = 29.24; 72% female). Participants were allocated to one of three hazard types (COVID-19 pandemic, violent acts, severe weather) and presented with warning messages that were previously issued via an official warning app. Four components of risk appraisal (perceived severity (PS), anticipated negative emotions (AE), anticipatory worry (AW), and risk perception (RP)) were assessed before and after presenting the warning message. Path models were calculated to predict the intention to comply with the warning message, controlling for age, gender, and previous hazard experience. Results: For the COVID-19 pandemic, higher age (β = .18) predicted warning compliance (R2 = .05). AE (β = .20) predicted compliance in case of violent acts (R2 = .09). For severe weather, PS (β = .28), age (β = .29), and female gender (β = .34) lead to higher compliance (R2 = .27). Changes across risk appraisal components were not consistent, as some facets decreased after the receipt of a warning message. Discussion: Risk appraisal has shown a marginal yet differential influence on warning message compliance in different types of hazards. Regarding the COVID-19 pandemic, the impact of sociodemographic factors on compliance should be studied more intensively. Moreover, integrating intermediary variables, such as self-efficacy, is necessary.